2022
DOI: 10.1029/2022jc018893
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Southern Ocean Cyclonic Eddy on Mesopelagic Micronekton

Abstract: Mesoscale eddies shape the foraging ecology of predators such as marine mammals and seabirds. A growing number of animal tracking studies show that predators alter their swimming, diving, and foraging behavior within mesoscale eddies. However, little is known about how Southern Ocean eddies influence the distribution of mesopelagic micronekton (fish, squid, and crustaceans), which are major prey items of megafauna. Studies in other oceanic regions have found that eddies can influence the abundance and communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…ESP3 is an acoustic data processing application developed by the National Institute of Water and Atmospheric Research (NIWA), New Zealand [16]. This application can be used freely for various acoustic data processing such as studies of gas leaks from underwater faults [17,18], abundance of marine organisms [19][20][21], and other studies within the scope of hydroacoustic [22][23][24]. Fish density calculations were conducted using the Microsoft Excel application based on the results of processing in ESP3.…”
Section: Analysing Hydroacoustic Datamentioning
confidence: 99%
“…ESP3 is an acoustic data processing application developed by the National Institute of Water and Atmospheric Research (NIWA), New Zealand [16]. This application can be used freely for various acoustic data processing such as studies of gas leaks from underwater faults [17,18], abundance of marine organisms [19][20][21], and other studies within the scope of hydroacoustic [22][23][24]. Fish density calculations were conducted using the Microsoft Excel application based on the results of processing in ESP3.…”
Section: Analysing Hydroacoustic Datamentioning
confidence: 99%
“…The CEs, related to cold core region, is actually a local aggregation zone of zooplankton and micronekton (Zimmerman and Biggs, 1999), typically characterized by high levels of primary productivity and plankton biomass due to nutrients upwelling in the core (Vaillancourt et al, 2003). The integrated and vertical distribution of the acoustic scattering inside the CEs was similar to its origin waters (Della et al, 2022). At the same time, there are cases where biomass in AEs has increased or decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that mesoscale eddies exhibit water properties that differ from those of the surrounding water (Della Penna et al., 2022; Frenger et al., 2015; Gaube et al., 2014; Sun et al., 2017, 2022; Sun, Dong, Tan, & He, 2019; Wang et al., 2021). Salinity anomalies exist within individual eddies as a result of the geostrophic depression and uplift of the background isopycnal surfaces associated with anticyclonic and cyclonic eddies, respectively (Della Penna et al., 2022; Dong et al., 2014; Frenger et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that mesoscale eddies exhibit water properties that differ from those of the surrounding water (Della Penna et al., 2022; Frenger et al., 2015; Gaube et al., 2014; Sun et al., 2017, 2022; Sun, Dong, Tan, & He, 2019; Wang et al., 2021). Salinity anomalies exist within individual eddies as a result of the geostrophic depression and uplift of the background isopycnal surfaces associated with anticyclonic and cyclonic eddies, respectively (Della Penna et al., 2022; Dong et al., 2014; Frenger et al., 2015). The salinity anomalies within eddies tend to move with mesoscale eddies, which usually feature nonlinearity and amplified velocities, due to the advective trapping of fluid contained in their interiors (Chelton et al., 2007; Dong et al., 2014; McGillicuddy, 2016).…”
Section: Introductionmentioning
confidence: 99%